Non-local Field Theory from Matrix Models - Banburski-Fahey, Andrzej; Lanier, Jaron; Shyam, Vasudev; Smolin, L.; Yargiç, Yĭgit (arXiv, 2022)
We show that a class of matrix theories can be understood as an extension of quantum ﬁeld theory which has non-local interactions. This reformulation is based on the Wigner-Weyl transformation, and the interactions take the form of Moyal (cid:63) -product on a doubled geometry. We recover local dynamics on the spacetime as a low-energy limit. This framework opens up the possibility for studying novel high-energy phenomena, including the uniﬁcation of gauge and geometric symmetries in a gauge theory.